2011
DOI: 10.20467/1091-5710.15.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Healing Environment: Nurse-to-Nurse Caring in the Critical Care Unit

Abstract: The purpose of this study was to explore with and empower nurses to create a healing environment. The study’s design was a combination study utilizing both quantitative and qualitative methods. The primary research question was, “How is the healing environment of the critical care units affected by the nurses’ trust and empowerment?” The Gibbs’TORI Self Scale and Gibbs’TORI Team Scale measured trust and Barrett’s Power as Knowing in Participation in Change Tool measured empowerment/power. The qualitative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…An empowering process requires engagement combined with nourishing and interactive relationships built on mutual trust and respect . Acknowledgement and encouragement are essential components in an empowering relationship, as are authenticity, sensitive communication, active listening, and equality, which means that everyone's experiences and feelings are important and of equal value . The possibility and support to express feelings, explore problems and develop solutions are facilitated within a positive, warm and supportive atmosphere with room for a caring spirit, joy and humour .…”
Section: Resultsmentioning
confidence: 99%
“…An empowering process requires engagement combined with nourishing and interactive relationships built on mutual trust and respect . Acknowledgement and encouragement are essential components in an empowering relationship, as are authenticity, sensitive communication, active listening, and equality, which means that everyone's experiences and feelings are important and of equal value . The possibility and support to express feelings, explore problems and develop solutions are facilitated within a positive, warm and supportive atmosphere with room for a caring spirit, joy and humour .…”
Section: Resultsmentioning
confidence: 99%
“…France et al. ( 2011 ) suggested that trust, mutual respect, mentoring, collegiality and camaraderie are necessary for creating a healing and supportive environment. Similar findings were yielded in this study, as Ps spoke of and were observed to live the values of support for each other, assist colleagues struggling with workloads, experiencing stressful moments or feeling overwhelmed, and working alongside new staff to ensure appropriate orientation to the unit.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses therefore need to care for each other. A suggested approach is nurse‐to‐nurse caring, which can create a healing environment in critical care where the empowerment and autonomy gained can actually counteract burnout and staff turnover (France, Byers, Kearney, & Myatt, ). In addition, it is recommended that orientation programs for novice critical care nurses focus on technological confidence (Despins, ) but this must be balanced in the concept of caring.…”
Section: Discussionmentioning
confidence: 99%